Tin deposits at Prebuz and Rolava in the Krusne Hory / Erzgebirge, Czech Republic: classic localities, new challenges - Rojik,P. (Journal of the Czech Geological Society, 2005)
The Czech part of the late-Variscan Karlovy Vary (Eibenstock) pluton in the Krusne hory (Erzgebirge) Mts. was studied with a focus on the problems of greisen tin deposits and their relationship to highly evolved granites. The paper is based on the author's detailed field work and research of mining history. Important tin deposits of greisen type are concentrated to a girth of an oval shape ("tin ring") situated on the Czech territory roughly in the centre of the outcrops of the younger granite suite (YIC granite). Tin deposits are spatially associated with the youngest highly evolved granites. Greisen zones intersect all the known types of granites and converge towards the depth. Tin contents decline with depth and laterally to the centre of the "tin ring". Centres of greisen zones enclose veinlets of cassiterite, lollingite, microcline, quartz, and hematite whose depth extension is unknown. This supports the concept of a tectonic predisposition of ore mineralization and of a deep source of tin, related to the source of the late intrusions of highly evolved granites. Certain porphyritic granite textures exhibit bimodality of the groundmass reminding of two-phase granite textures developed under subvolcanic conditions. In places, a rhytmical layering (banding) of granites of the older and younger suite was observed.
Keywords: Karlovy Vary pluton; Eibenstock pluton; Krusne hory; Erzgebirge; greisens; subvolcanic granites; layered granites